Prevalence and biostatistical analysis of health facility related predictors of adherence to healthy timing and spacing of pregnancy among multiparous women in Wajir County, Kenya - Okenyoru, Douglas Sendora; Matoke, Vincent; Waititu, Hellen (International Journal Of Community Medicine And Public Health, 2026)
Background: Globally, healthy timing and spacing of pregnancy is important for reducing maternal and child health risks, yet adherence remains unpredictable. Sub-Saharan Africa faces high rates of short birth intervals due to inadequate contraception, cultural norms, and weak health systems. In Kenya, and especially Wajir County, poor adherence is driven by low contraceptive uptake, high fertility, and early pregnancies. Methods: The study employed a cross-sectional descriptive-analytical design. It included multiparous women. A sample of 368 participants was selected using Fisher’s formula via systematic sampling. Data were collected with structured questionnaires and analyzed using SPSS version 26.0. Results: The results revealed that 56.5% of respondents adhered to heathy timing and spacing of pregnancy in Wajir County with 34.2 under age pregnancy, 15.8% abortion/miscarriage and 32.6% short inter-birth interval. The predictors of adherence based on health facility related factors were; time taken to reach nearest health facility offering family planning services (AOR=0.464, p=0.016), ever missed family planning services due to stock-out (AOR=3.902, p=0.001) and availability of contraceptive at health facilities (AOR=2.768, p=0.013) significantly influenced the adherence. Conclusions: The study found that the health facility related factors that predicted the adherence were; time taken to reach nearest health facility offering family planning (AOR=0.464, p=0.016), ever missed family planning services due to stock-out (AOR=3.902, p=0.001) and availability of contraceptive at health facilities (AOR=2.768, p= 0.013).